DIFFERENT TYPES OF WRITING PROSECC - Sattorova Ruxshona Sobirjon qizi; Zoirova Dilfuza Xayriddinovna (TADQIQOTLAR.UZ, 2024)
Annotation:  Different types of writing have distinct process tailored to their purposes and audiences. The writing prosecc can vary depending on the type of writing being done, but it generally follows a set of stages that help organize thoughts and product clear effective work.